Healthy diets and the role of micro, small, and medium enterprises: Examining Ethiopia’s food environment - de Brauw, Alan; Hirvonen, Kalle (International Food Policy Research Institute, 2025)
Micro, small, and medium enterprises (MSMEs) play an important role in the food environment in many low- and middle-income countries. But there is little systematic knowledge about the opportunities they have and constraints they face in trying to grow their businesses. To contribute to building this knowledge base, we draw upon linked household–enterprise surveys collected in two districts in Ethiopia in 2023. To learn about the constraints faced by these enterprises, we examine differences in organizational characteristics and business practices by outlet type, location, and manager gender and education among MSMEs that sell food. The results suggest that while there are clear availability constraints for specific types of foods, there are some strategies that could help MSMEs that retail healthy foods increase sales. If policymakers or others are interested in supporting sales through the food environment, interventions such as business training, service access, and capacity building on nutrition would best fit their needs.